2021
DOI: 10.3389/fenvs.2021.715350
|View full text |Cite
|
Sign up to set email alerts
|

We Can Better Manage Ecosystems by Connecting Solutions to Constraints: Learning from Wetland Plant Invasions

Abstract: Wetlands provide critical wildlife habitat, improve water quality, and mitigate the impacts of floods, droughts, and climate change. Yet, they are drained, filled, dredged, and otherwise altered by humans, all of which contribute to their high susceptibility to plant invasions. Given the societal significance of wetlands and the disproportionately large amount of time and money spent controlling invaders in remaining wetlands, a fundamental shift must occur in how we approach restoration of plant-invaded wetla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 232 publications
(451 reference statements)
0
4
0
Order By: Relevance
“…The science‐practice gap has been identified as a widespread problem in restoration research and practice (Matzek et al 2014; Adams et al 2021). Surprisingly, in our study we found that a large portion of vendors access peer‐reviewed literature to gain knowledge to facilitate production.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The science‐practice gap has been identified as a widespread problem in restoration research and practice (Matzek et al 2014; Adams et al 2021). Surprisingly, in our study we found that a large portion of vendors access peer‐reviewed literature to gain knowledge to facilitate production.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, in our study we found that a large portion of vendors access peer-reviewed literature to gain knowledge to facilitate production. This finding suggests that the scientific community could play a strong role in improving wetland plant material availability, especially if research results are freely available through open access publication (Adams et al 2021). Scientists could also engage vendors for input on designing relevant research (i.e.…”
Section: Strategies To Improve Species Availabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Capacity challenges such as adequate funding, labor, retaining people with expertise, and agency priorities have also been suggested as potential barriers to revegetation (Galatowitsch 2023). In particular, insufficient and unpredictable funding, as well as a lack of appreciation of the funding requirements for restoration implementation have been cited as potential obstacles in wetland restoration (Adams et al 2021). Additionally, previous research has shown an overall lack of diverse plant materials available for revegetation, which suggests that access to plant materials may also be a challenge for wetland land managers (National Academies of Sciences, Engineering, and Medicine 2023; Henry et al 2024).…”
Section: Introductionmentioning
confidence: 99%